Relevance of SMS Advertisement for Brand Managers Applying Theory of Reasoned Actions - Kongpan, Yenjit; Sirikamonsin, Patsara; Li, Hang; Potimu, Kittipong (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the study is to examine the impact of entertainment, informativeness, irritation and credibility on attitude towards SMS advertisement. The target population was Malaysian consumers of products and service who have experienced SMS advertisement. However, sample size was based on 316 responses. The current study has aimed to use convenience sampling in selecting the participants. Also, the current study has applied PLS- SEM analysis technique using SmartPLS version 3.2.8 to test hypothesis. In addition, results show that entertainment was not affecting attitude towards SMS Advertisement. But, informativeness and credibility were significantly affecting the attitude towards SMS Advertisement. However, irritation was not affecting the attitude towards SMS advertisement. Moreover, managerial implication of this research is firstly, in order to overcome the entertainment constraints of SMS messages, advertisers may need to use skip able ads which brings SMS messages to the next stage and requires visual elements such as pictures and videos as well as sound to be included. Similarly, as the study shows the significant impact of credibility so in order to ensure the advertisement's credibility, advertisers should provide consumers with the precise information they want and not something they may view as spam.